PENGAMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS WEBSITE BERBANTUAN GEOGEBRA PADA MATERI SPLDV - Armila, Sely; Amrullah; Gilang Primajati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to develop a GeoGebra-assisted website-based learning media on the topic of Systems of Linear Equations in Two Variables (SLETV) that meets the criteria of validity, practicality, and effectiveness. The study employed a Research and Development (R&D) method using the 4D development model consisting of the define, design, develop, and disseminate stages. The research was conducted at SMPN 14 Mataram with eighth-grade students as the research subjects. Data were collected using expert validation sheets, teacher and student response questionnaires, and learning achievement tests. The results showed that the developed learning media obtained an average validity score of 77.7%, consisting of 79.7% from media experts and 75.7% from subject matter experts, indicating that the media was valid. The practicality test yielded an average score of 83.2%, with 84.74% from students and 81.65% from teachers, categorized as very practical. Furthermore, the effectiveness test showed an average N-Gain score of 0.648 (64.8%), indicating a moderate improvement in students’ learning outcomes. Therefore, the developed website-based learning media assisted by GeoGebra is considered valid, practical, and effective for supporting mathematics learning on the topic of Systems of Linear Equations in Two Variables.